Issledovanie funkcional'noj motornoj asimmetrii lyžnikov-gonšcikov v aspekte profilaktiki travmatizma - Ignatyeva, L. E.; Chetaykina, O. V. (Vestnik sportivnoj nauki; Sports science bulletin, 2020)
The article considers functional motor asymmetry as a factor in injuries in skiing. Diagnostics of motor asymmetry were carried out using a battery of tests, dynamometry, and light-optical diagnostics of posture and muscle imbalance using DIERS Formetric 4D technology. The study revealed the characteristics of the psychophysical organization and muscle imbalance formed during the training process. Specific motor activity based on genetically determined motor preferences has led to characteristic disorders of the musculoskeletal system.